Egypt, Saudi Arabia and the UAE: The end of an alliance. Divergences of interest in bilateral relations offer opportunities for Germany and the EU - Stephan Roll (Stiftung Wissenschaft und Politik (SWP), 2023)
Over the past 10 years, the de facto alliance of the governments of Egypt, Saudi Arabia and the United Arab Emirates has exercised significant influence over developments in the Middle East. The common goal has been to prevent democratic transformation, stop the rise of political Islam and counter the influence of Iran and Turkey over the region. But joint regional political interventions have so far had little success. Moreover, divergences of interest in bilateral relations between these authoritarian Arab states have come to light in recent months. The potential for conflict has become evident with regard to both economic and regional political issues and is only likely to increase in the future. For Germany and the European Union, these divergences of interest between the three countries offer an opportunity to pursue their own goals in the region.
Additional information: Corrected version, dated 23 August 2023
Keywords: 320; Egypt; Saudi Arabia; UAE; Iran; Turkey; Germany; EU; Middle East; political Islam; democratic transformation